When Learning Readiness Fails to Predict Science Conceptual Understanding: Structural Evidence from Elementary Education in the Society 5.0 Era - Raihan, Primus Devra; Hastuti , Woro Sri; Mustadi , Ali; Munfariqoh, Aqidatul; Rizal, Ahmad Saiful; Setyoningsih, Rosantika Utami; Setiani, Hasnah (Journal of Education Culture and Society, 2026)
Aim. This study examines whether learning readiness functions primarily as a direct cognitive engine of science conceptual understanding or more strongly as an enabling behavioural infrastructure that supports students’ participation in learning processes among fourth-grade students in the Society 5.0 context.Methods. A quantitative explanatory design was employed. Data were collected from 320 Grade 4 students in public elementary schools and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The model integrates Learning Readiness, Digital Capability, Learning Motivation, and Self-Directed Learning as learning process constructs, and Science Conceptual Understanding as a higher-order cognitive construct reflected by Physical Changes, Force and Motion, and Life and Environment.Result. The findings reveal a pronounced structural asymmetry. Learning Readiness strongly predicts Digital Capability, Learning Motivation, and Self-Directed Learning, explaining approximately 70–80% of the variance in learning behaviour, yet demonstrates negligible explanatory power for Science Conceptual Understanding. In contrast, Science Conceptual Understanding demonstrates strong internal coherence across its domains, indicating a stable higher-order cognitive structure. The findings further suggest that behavioural readiness alone may not be sufficient to directly support conceptual mastery under constrained digital and instructional conditions.Conclusion. These results indicate that while learning readiness effectively shapes students’ behavioural engagement in learning, conceptual understanding appears to depend more strongly on instructional quality, inquiry-oriented pedagogy, conceptual scaffolding, and pedagogically guided science learning experiences within elementary classrooms.Cognitive value. This study repositions learning readiness not simply as a direct cognitive engine of conceptual mastery, but as an enabling behavioural infrastructure whose contribution to conceptual understanding may be shaped by broader instructional and pedagogical conditions in Society 5.0-oriented elementary science education.